Evidence-based statin prescription for cardiovascular protection in renal impairment - Fabbian, Fabio; De Giorgi, Alfredo; Pala, Marco; Tiseo, Ruana; Manfredini, Roberto; Portaluppi, Francesco (Clinical and experimental nephrology, 2011)
Dyslipidemia is a well-known risk factor for cardiovascular disease in the general population, and the cardioprotective role of statins is well established. However, although cardiovascular disease is the major cause of morbidity and mortality in chronic kidney disease (CKD), the role of statin therapy is still under investigation. In CKD the atherosclerotic burden is high and pathophysiology of dyslipidemia is complex; however, the majority of large-scale statin trials excluded patients with CKD. Statins could have different effects in the different stages of CKD. Two large trials involving haemodialysis patients showed unfavourable results, whereas in renal transplant subjects as well as in early CKD subjects, statins reduced cardiovascular risk. The studies involving early CKD patients are post-hoc analyses of large trials and they showed that statins are more effective in secondary than in primary prevention. The aim of this study was to evaluate the effectiveness of statins for prevention of cardiovascular events by calculating the number of patients needed to be treated in different interventional trials. We conclude that dyslipidemia is a modifiable cardiovascular risk and statins appear to be an effective treatment especially in the early stages of CKD. Patients on renal replacement therapy could obtain an advantage from this treatment; however, the patient’s clinical prognosis should be taken into account when evaluating treatment.